Management of Hajj Funds in Sukuk Investment from an Islamic Economic Perspective - Maulana, M. Rifka; Mawadah, Sokhikhatul (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2023)
One of the impacts of the Covid-19 pandemic is the cancellation of Hajj departures in Indonesia in 2020, based on the Decree of the Minister of Religion (KMA) Number 494 of 2020. The delay in the departure of the Hajj even though the more pilgrims register for Hajj, the more funds will be received. Banks cannot manage that much haj funds, so they are stored in state sukuk. Hajj funds are managed in State Sharia Securities (SBSN) or State Sukuk by the Ministry of Religion through the Hajj Management Financial Management Agency (BPKH). How is the management of Hajj funds on state sukuk, is it effective or not. This research is a qualitative research with literature study. The results of this study are that the mechanism for managing Hajj funds begins with the way pilgrims register and pay. After the funds have been collected, the BPKH manages the money through each congregation's account at the bank. Fund management exists in several placements, one of which is sukuk. Placement in this sukuk is good but not optimal when viewed from the yields obtained, but when viewed from the risks faced, this sukuk investment is very effective. Research can be used as a reference source for parties who need information about the management of Hajj funds, especially for pilgrims who are waiting for the pilgrimage to depart.